2021
DOI: 10.48550/arxiv.2101.07699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When are LIGO/Virgo's Big Black-Hole Mergers?

Maya Fishbach,
Zoheyr Doctor,
Thomas Callister
et al.

Abstract: We study the evolution of the binary black hole (BBH) mass distribution across cosmic time. The second gravitational-wave transient catalog (GWTC-2) from LIGO/Virgo contains BBH events out to redshifts z ∼ 1, with component masses in the range ∼ 5-80 M . In this catalog, the biggest black holes, with m 1 45 M , are only found at the highest redshifts, z 0.4. We ask whether the absence of high-mass BBH observations at low redshift indicates that the astrophysical BBH mass distribution evolves: the biggest BBHs … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…Fitting a population model that allows the mass distribution to evolve with redshift, Fishbach et al (2021) found a mild preference that the rate increases more steeply from z = 0 to z = 1 for heavier BBH systems compared to lighter systems. The orange band of Figure 6 shows κ = ln(R1/R0) ln 2 as a function of primary mass, inferred using the evolving broken power law model of Fishbach et al (2021). We can use these results to infer different time delay distributions and/or progenitor formation rates as a function of BBH mass.…”
Section: Effect Of Black Hole Massmentioning
confidence: 99%
See 3 more Smart Citations
“…Fitting a population model that allows the mass distribution to evolve with redshift, Fishbach et al (2021) found a mild preference that the rate increases more steeply from z = 0 to z = 1 for heavier BBH systems compared to lighter systems. The orange band of Figure 6 shows κ = ln(R1/R0) ln 2 as a function of primary mass, inferred using the evolving broken power law model of Fishbach et al (2021). We can use these results to infer different time delay distributions and/or progenitor formation rates as a function of BBH mass.…”
Section: Effect Of Black Hole Massmentioning
confidence: 99%
“…The blue band corresponds to the model of Section 2 in which the mass distribution is independent of redshift. The orange band corresponds to a model in which the mass distribution can evolve with redshift, from Fishbach et al (2021). Solid lines denote medians and shaded bands denote central 50% and 90% credible intervals.…”
Section: Effect Of Black Hole Massmentioning
confidence: 99%
See 2 more Smart Citations
“…260 Measuring the evolution of the mass and/or spin distribution with redshift could also reveal subpopulations of higher generation mergers. 261 Beside phenomenological models that search for trends in the BH component mass, mass ratio and spin distribution, data analysis strategies based on physical coagulation models have also been successfully employed. 194,196,262,263 These methods typically parameterize the population of first-generation BHs with a phenomenological model and introduce additional parameters calibrated on cluster simulations to model the coagulation process and production of higher generation mergers.…”
Section: Outliers and Subpopulationsmentioning
confidence: 99%